2021
DOI: 10.1101/2021.11.23.469695
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antiviral activity of Molnupiravir precursor NHC against SARS-CoV-2 Variants of Concern (VOCs) and implications for the therapeutic window and resistance

Abstract: SynopsisBackgroundThe UK Medicines and Regulatory Healthcare Agency (MHRA) have recently licensed the anti-viral drug, molnupiravir, for use in patients with mild-moderate COVID-19 disease with one or more risk factors for serious illness. Treatment with anti-viral drugs is best initiated early to prevent progression to severe disease, although the therapeutic window for intervention has not yet been fully defined.ObjectivesThis study aimed to determine the activity of the molnupiravir (NHC) to different SARS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
(64 reference statements)
2
4
0
Order By: Relevance
“…Inhibitory values were similar for all VOC tested and ranged from 0.27 (omicron) to 0.62 (alpha) µM, which closely resembled that against the original SARS-CoV-2 isolate 18,24 . Consistent with other cell culture data 16 , also VOC delta was highly sensitive to treatment (EC50 0.33 µM).…”
Section: Main Textsupporting
confidence: 91%
See 2 more Smart Citations
“…Inhibitory values were similar for all VOC tested and ranged from 0.27 (omicron) to 0.62 (alpha) µM, which closely resembled that against the original SARS-CoV-2 isolate 18,24 . Consistent with other cell culture data 16 , also VOC delta was highly sensitive to treatment (EC50 0.33 µM).…”
Section: Main Textsupporting
confidence: 91%
“…In the absence of controlled clinical data assessing molnupiravir efficacy against omicron, it is currently unclear to what degree the dwarf hamster-derived results extend to human therapy. Our study demonstrates, however, that pharmacological mitigation of severe COVID-19 is complex and that attempts to predict drug efficacy based on unchanged ex vivo inhibitory concentrations alone 16 may be premature. The dwarf hamster-based results alert to the need to continuously reassess therapeutic benefit of approved antivirals for individual patient subgroups as SARS-CoV-2 evolves and potential future VOC may emerge.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…As per the news reports, India-based enterprise Glenmark has secured government approval for the large-scale manufacturing and antiviral Favipiravir drug to treat SARS-CoV-2 infected patients [ 27 ]. Furthermore, molnupiravir parent drug (NHC) combination of drugs against SARS-CoV-2 viruses are recommended in a trial version of the treatment plan [ 28 ], including ritonavir/ralproveravir or ribavirin by intravenous injection in addition to the inhalation of alpha interferon [ 26 ]. Another example is the cheap and widely-available steroid drug called Dexamethasone, pushed by UK experts as a potential treatment of SARS-CoV-2 infection, with suggestions signifying great success in reducing deaths up to a third in patients showing severe symptoms, thus proving it to be a life-saving drug [ 29 ].…”
Section: Therapeutic Interventionsmentioning
confidence: 99%
“…NHC can base pair with guanosine, but also with adenosine, thus leading to multiple errors in the subsequently synthesized viral RNA genomes and resulting in replication-deficient virus particles. Molnupiravir is active against SARS-CoV-2 replication in vitro and in vivo (Rosenke et al, 2021;Sheahan et al, 2020;Wahl et al, 2021), and this includes the recently emerged Omicron variant (Prince et al, 2021;Vangeel et al, 2021). It also prevents SARS-CoV-2 transmission in the ferret model (Cox et al, 2021), and it was found clinically effective in large-scale clinical trials (Jayk Bernal et al, 2021;Painter et al, 2021), exemplified by the trials registered at clinicaltrials.gov with the numbers NCT04575584, NCT04575597 and NCT04405739, leading to approval in the UK.…”
Section: Introductionmentioning
confidence: 99%